3(y-6x)=12

Simple and best practice solution for 3(y-6x)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-6x)=12 equation:


Simplifying
3(y + -6x) = 12

Reorder the terms:
3(-6x + y) = 12
(-6x * 3 + y * 3) = 12
(-18x + 3y) = 12

Solving
-18x + 3y = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-18x + 3y + -3y = 12 + -3y

Combine like terms: 3y + -3y = 0
-18x + 0 = 12 + -3y
-18x = 12 + -3y

Divide each side by '-18'.
x = -0.6666666667 + 0.1666666667y

Simplifying
x = -0.6666666667 + 0.1666666667y

See similar equations:

| 7d+9=23 | | 2a-3=19 | | 3b+1=-8 | | -8+7k=69 | | 2b+10=-6 | | -7k+1=-20 | | -4d+4=-32 | | 6k+6=36 | | 10-7b=52 | | -4k+10=-34 | | 5-3d=-13 | | -5m+9=-51 | | -7n-6=-69 | | 2k-7=9 | | -6b+1=-53 | | -2d-9=-13 | | 3+4k=-33 | | 2+4m=2 | | 1-3m=-26 | | 5x(3x-2)=0 | | -8-6m=-80 | | -4d-8=-52 | | 7d+4=-24 | | -6t-10=-34 | | 1(x)=2x-1 | | 2n-6=-16 | | 1+7x=-83 | | -6m-7=-31 | | 4-2n=-14 | | 2n+9=-9 | | -3a+7=19 | | 4n+1=-3 |

Equations solver categories